Distilling design methodologies for additive manufacturing from case studies - Ricardo Simian (FORMakademisk)
Additive manufacturing (AM) is a palette of digital fabrication tools which has quickly established itself as one of the key prototyping methods used during design development processes. Nevertheless, end product applications of AM are rare and usually limited to high end customised niches, such as medical implants or one of a kind, expensive and high-performance objects (Attanasio, 2022). The lack of more daily examples of successful AM end products despite a matured technology raises the question whether there are no real niches for AM end products or if designers have not yet been able to identify and address them. We argue that a lack of suitable design methodologies (DM) integrating modern understanding of AM is at least partially responsible for the lack of progress. In this paper we analyse the current state of AM applications for end product manufacturing and propose a bottom-up approach for creating AM for DM from case studies to address the lack of available literature in the field.